2021
DOI: 10.1016/j.nicl.2021.102769
|View full text |Cite
|
Sign up to set email alerts
|

Automated multiclass tissue segmentation of clinical brain MRIs with lesions

Abstract: Highlights A U-Net incorporating spatial prior information can successfully segment 6 brain tissue types. The U-Net was able to segment gray and white matter in the presence of lesions. The U-Net surpassed the performance of its source algorithm in an external dataset. Segmentations were produced in a hundredth of the time of its predecessor algorithm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 47 publications
2
16
0
Order By: Relevance
“…Our results corroborate previous studies that deep learning is effective in medical image segmentation. 2123,27,28 This study also replicated the results of prior studies showing that U-Nets can segment brain images with high accuracy. 23,27 Our results also corroborate a previous study that showed the effectiveness of 2D CapsNets for segmenting biomedical images, outperforming other deep learning models including U-Nets.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…Our results corroborate previous studies that deep learning is effective in medical image segmentation. 2123,27,28 This study also replicated the results of prior studies showing that U-Nets can segment brain images with high accuracy. 23,27 Our results also corroborate a previous study that showed the effectiveness of 2D CapsNets for segmenting biomedical images, outperforming other deep learning models including U-Nets.…”
Section: Discussionsupporting
confidence: 85%
“…2123,27,28 This study also replicated the results of prior studies showing that U-Nets can segment brain images with high accuracy. 23,27 Our results also corroborate a previous study that showed the effectiveness of 2D CapsNets for segmenting biomedical images, outperforming other deep learning models including U-Nets. 8 A subsequent study showed that 2D CapsNets were less effective in segmenting heart and brain MRI slices.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…There are different strategies in transfer learning in terms of how the layers are transferred (e.g., directly, fine-tuned, or reinitialized) (Kalmady et al, 2021 ; Prakash et al, 2021 ; Ren et al, 2021 ; Wang et al, 2021 ; Weiss et al, 2021 ). For example, in CNN, there are convolution layers and fully-connected (FC) layers and in transfer learning one can transfer weights associated with convolution layers, FC layers, or both, then decide to freeze or fine-tune them.…”
Section: Resultsmentioning
confidence: 99%